To donate or not to donate? How cosmopolitanism and brand anthropomorphism influence donation intentions for international humanitarian causes. Issue 4 (30th August 2021) - Dalman, M. Deniz; Ray, Subhasis
Abstract : Purpose: There are vast opportunities for nonprofit organizations (NPOs) globally to find support for international humanitarian causes. However, donors/consumers are not always willing to contribute for such causes. This study aims to investigate how potential donor perceptions are shaped to gain wider support and aims to build a model that could guide managers of NPOs in their communication strategy. Design/methodology/approach: Two scenario-based experiments with the participation of graduate students from an Indian university were conducted. Findings: Cosmopolitan people have the higher moral judgment of the international causes championed by NPOs. However, anthropomorphizing the NPO's message elevates the moral judgments among non-cosmopolitans. Process tests indicate that these moral judgments indirectly impact donation intentions for these causes. Research limitations/implications: The paper only investigates donation intention for poverty and not humanitarian causes such as access to drinking water. Moreover, the campaign chosen takes place only in Africa (e.g. not in Asia or Latin America). Practical implications: NPOs could tailor their marketing messages for international humanitarian causes by targeting cosmopolitan donors/consumers and using humanization as the branding strategy. Originality/value: This research contributes to theory by showing how consumers who would otherwise not contribute to an out-group could be influenced positively by the NPOs' branding strategy.